Accounting for context: Exploring the role of objects and spaces in the consumption of alcohol and other drugs - Duff, Cameron (2012)
This paper addresses some of the major implications of actor-network theory (ANT) for research on the consumption of alcohol and other drugs (AOD). It focuses on the significance of ANT's rejection of the subject-object distinction for recent debates in human and cultural geography regarding the role of social contexts in mediating the character and experience of AOD consumption. In exploring this theme, I apply insights derived from the work of Bruno Latour and John Law to the analysis of qualitative data recently collected in studies of AOD use in Melbourne, Australia and Vancouver, Canada. These studies indicate that AOD consumption is a relational achievement involving diverse objects, spaces, actors and affects. The paper goes on to argue that social contexts may themselves be understood as discrete assemblages of such objects, spaces and actants. This suggests a novel basis for investigating the role of social contexts in mediating AOD consumption in particular sites and settings. The paper closes with an assessment of the implications of these arguments for the ongoing design of novel, place-based approaches to the study of AOD use within human and cultural geography. I emphasise the need for greater recognition of the agentic force of spaces, objects and actants, such that research designs more sensitive to the dynamics of context might be elaborated. © 2012 Copyright Taylor and Francis Group, LLC.